PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR AKTIVA, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL - Fitri Lim; Hesty Ervianni Zulaecha; Hamdani, Hamdani; Sriyanto, Sriyanto (Akuntansi, 2022)
The purpose of this article is to analyze the significance of the influence of profitability, liquidity, asset structure and company size on capital structure. This research was conducted at Food and Beverage Companies on the Indonesia Stock Exchange (IDX) for the 2015-2021 period. The sampling technique used purposive sampling technique. Based on predetermined criteria, 8 companies were obtained. The type of data used is secondary data, namely through financial report data published on the website www.idx.co.id. The analytical method used is panel data logical regression analysis. The results of the study show that partially Profitability does not have a negative impact on Capital Structure. Liquidity has a negative impact on Capital Structure. Company Size does not have a negative impact on Capital Structure. Asset Structure does not have a negative impact on Capital Structure. Based on the results of the simultaneous analysis, Profitability, Liquidity, Company Size, and Asset Structure have a positive effect on Capital Structure.